Basic structure and system of values - Ahmed Shogar, Ibrahim Adam (2013)
The world as appears to mankind is consisting of two parts: facts and values. The proper growth and development of human community is mainly based on their awareness of these two aspects of human life. The former constitutes the enterprise of scientific knowledge and the later gives meaning to the world round us. Facts are based on observation and experience of the physical world, while values are based on our judgments to things happening around us. These two aspects of the world have guided human attention, throughout the history, to develop the two basic forms of research area: investigation of the natural phenomenon and study of human conduct. Regardless of their sources, knowledge and values are the general approaches of mankind to conceptualize the world as evidently reflected by various civilizations of human history. Values can be divided based on many factors, among which are the division into moral, aesthetic, and intellectual. As we need science to understand the world, also it is essential to have values which guide to use the scientific knowledge for the betterment of mankind. The main objective of this paper is to highlight the basic structure of theory of values, with especial reference to the Islamic values system.